Study of the Qualitative Composition and Quantitative Content of Parthenolide in the Feverfew (Tanacetum Parthenium) Herb Cultivated in Ukraine - Hordiei K. R.; Gontova T. N.; Gubar S. N.; Yaremenko M. S.; Kotova E. E. (Sciendo, 2021)
Feverfew is a well-known medicinal plant as a source of the sesquiterpene lactones, the main one is a parthenolide (about 85%). Owing to the parthenolide, feverfew herb has anti-inflammatory activity and it is widely used for prevention of migraine. The aim was to study the qualitative composition and quantitative content of the parthenolide in the samples of the feverfew herb cultivated in Ukraine and to study the influence of environmental factors on the accumulation of parthenolide.